Pengaruh Komponen Produk Wisata Terhadap Keputusan Berkunjung Ke Aeroxspace Bali (Jurnal Destinasi Pariwisata, 2025)
This study aims to analyze the influence of tourism products on visitors’ decision to visit AeroXSpace Bali, focusing on five key dimensions: attractions, facilities, accessibility, destination image, and price. Using a quantitative approach with purposive sampling, the research involved 123 respondents who had visited AeroXSpace at least once. Data were collected through a Likert-scale questionnaire tested for validity and reliability, with a minimum Cronbach’s alpha coefficient of 0.6, and analyzed using SPSS version 23 through multiple linear regression, partial t-tests, simultaneous F-tests, and the coefficient of determination. The findings reveal that, simultaneously, all tourism product variables significantly influence the decision to visit; however, partially, only destination image and price show a significant effect, with price emerging as the most dominant factor. These results highlight that while adequate attractions, facilities, and accessibility are important foundations for an artificial tourism destination, a positive destination image and competitive pricing strategies play a more decisive role in shaping tourists’ visit decisions, suggesting the need for AeroXSpace to maintain its innovative and safe brand image while implementing effective pricing policies to attract more visitors amidst competition in Bali’s tourism market.